2021
DOI: 10.3390/agriculture11070619
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile, Low-Power and Low-Cost IoT Device for Field Data Gathering in Precision Agriculture Practices

Abstract: Spatial and temporal variability characterization in Precision Agriculture (PA) practices is often accomplished by proximity data gathering devices, which acquire data from a wide variety of sensors installed within the vicinity of crops. Proximity data acquisition usually depends on a hardware solution to which some sensors can be coupled, managed by a software that may (or may not) store, process and send acquired data to a back-end using some communication protocol. The sheer number of both proprietary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…On one hand, some proposals combine different wireless technologies. The work in [24] allows the use of different technologies but the transceiver for wireless communication needs to be changed according to the desired technology. The work in [23] includes RFID and QR for the identification of the irrigation facilities but it needs the user to walk or drive at a close distance to access the information.…”
Section: System Characteristics Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, some proposals combine different wireless technologies. The work in [24] allows the use of different technologies but the transceiver for wireless communication needs to be changed according to the desired technology. The work in [23] includes RFID and QR for the identification of the irrigation facilities but it needs the user to walk or drive at a close distance to access the information.…”
Section: System Characteristics Comparisonmentioning
confidence: 99%
“…The proposal in [24] included some type of electrical error recovery that was not specified in detail. However, our proposal incorporates fault tolerance and recovery considering all the possible forms of malfunction that can affect the system.…”
Section: System Characteristics Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of small data collecting units has been rapid in recent years as they can cover data details for broad coverage, enhancing understanding of crop spatial and temporal variability [40]. Sensors with smaller dimensions, lower costs, and higher performance that can be deployed and integrated into production processes allow for more data and, ultimately, more information [41].…”
Section: Wetmentioning
confidence: 99%
“…A significant number of research works related to PA are found in the state of the art. Specifically, the systems that use Wireless Sensor Networks (WSNs) [ 8 ], have been widely tested in diverse crops, under different conditions [ 13 , 14 , 15 , 16 ]. Some of the works are focused on evaluating the network structure in terms of coverage range, throughput, latency or consumption, among other common parameters related to electronic design and communication techniques.…”
Section: Introductionmentioning
confidence: 99%